Analysis of E-Commerce Adoption Level on Culinary Micro, Small and Medium Enterprises (Umkm) in Karawang Regency Using Smart Pls (Buana Information Technology and Computer Sciences (BIT and CS), 2021)
E-commerce is an electronic trading tool where trading transactions, both buying and selling, are carried out electronically on the internet network. The existence of the internet and various technologies in the telecommunication sector have changed many things, one of which is in UMKM. The current owners of UMKM are expected to be able to compete and maintain the continuity of their business by making changes and applications in the technical field. This study aims to analyze the level of e-commerce adoption in culinary UMKM in Karawang Regency. The method used is a qualitative approach by measuring technology, environmental, organizational, and e-commerce adoption variables on the performance of UMKM. The data collection technique used in this study was probability sampling, with random sampling types, with a total of 70 culinary UMKM in Karawang regency. The results of this study indicate that technology and environmental factors have a positive effect on the adoption of e-commerce so that they can improve the performance of the UMKM in this study.